Antitumor activity of methanolic extract of Cyclea peltata - Meena J; Santhy Anandan (International Journal of Phytomedicine, 2015)
Phytocompound based drugs are soon gaining popularity as alternates for treatment of chronic and serious illness. Cyclea peltata has largely been classified as medicinal plant and used to treat various illness. Soxhlet based extraction of the plant was carried out using various solvents and subjected to chromatographic analysis to understand the variety of phytoconstituents present in the crude extract of the plant. Invitro and invivo testing for anticancer activity of the methanolic extract of the plant revealed potent significance among the haematological and cytotoxic parameters. The results, thus, indicate efficacy for anticancer activity although the main constituent of the crude extract is yet to be established.